Penerapan Putusan Arbitrase Internasional Ditinjau dari Undang-Undang dan Hukum Acara di Indonesia - Lu Sudirman; Ritaningtyas Ritaningtyas (Fakultas Hukum, Universitas Internasional Batam, 2016)
This research to determine the application of the decision of the International arbitration in resolving disputes in Indonesia based on Law No. 30of 1999 on arbitration and dispute resolution as well as procedural law in Indonesia. This research is a juridical normative legal research using comparative law method. Therefore the source of data used was a secondary data source which were gathered with literature review technique. Upon the gathering of the data, such data was processed and analized with analitic qualititative descriptive method, meaning that by grouping of data in accordance to the aspect studied and afterwards the conclusion was drawn and descriptively elaborated. The result conclude that International arbitration decision can be implemented in Indonesia if it is approved by the Chairman of the Central JakartaDistrict Court. Where the decision of the international arbitration is a dispute in the areas of commercial law and does not violate public order throughout the country Indonesia. Where the law number 30 of 1999 on arbitration and dispute resolution and the Supreme Court Regulation No. 1 of 1990 on procedures of foreign arbitral awards, still leave a gap to the Central Jakarta District Court to reject or annul the decision of international arbitration in Indonesia. With the enactment of Supreme Court Regulation No. 1 of 1990, the Indonesia ratified the New York Convention in 1958 concerning the recognition and enforcement of foreign arbitral award or international arbitration. It is thus an international arbitration ruling can be implemented or cannot be implemented in Indonesia